Assessment and determinants of aesthetic discomfort in hand osteoarthritis. Issue 1 (6th September 2011) - Hodkinson, Bridget; Maheu, Emmanuel; Michon, Mathilde; Carrat, Fabrice; Berenbaum, Francis
Abstract : Background: Dissatisfaction with hand appearance is frequently the presenting complaint of patients with hand osteoarthritis (HOA), yet no tool exists for its measurement and few studies have examined aesthetic discomfort. Objectives: The aims of this study were to measure the extent and to explore the associations of aesthetic concerns in HOA. Methods: 172 patients with HOA were assessed with tender joint and node count, global and pain scores, Functional Index for Hand Osteoarthritis, Short Form-12, Hospital Anxiety and Depression Scale and posterior–anterior hand radiographs. Patients scored the aesthetic impact of the disease on a Visual Analogue Scale of 0–100 mm and were classified into low, intermediate and high aesthetic concern (HAC) based on this score. Results: Of 172 patients (155 women), the majority (92%) had nodes and 46% had erosive disease. The mean aesthetic score was 44.8 mm (SD 35.9), and 59 (34.3%) patients scored their aesthetic discomfort ≥66 mm. Factors associated with HAC were female gender, a high number of tender joints and nodes, high global and pain scores, high radiological damage scores, the presence of erosions and high depression and anxiety levels. The multivariate analysis identified two independent factors associated with HAC: patient's global assessment (p=0.0005) and radiographic erosions (p=0.03). Conclusions: Aesthetic discomfort is a major concern for a significant number of patients with HOA, particularly women, those with a high burden of HOA disease and those with erosive osteoarthritis, and is also associated with depression, anxiety and poor health-related quality of life.